Fir Tussock Moth Orgyia detrita Guérin-Méneville, 1831 (Lepidoptera: Erebidae: Lymantriinae) - Donald W. Hall; Lyle Buss (EDIS)
This document provides an in-depth profile of the fir tussock moth (Orgyia detrita), focusing on its distribution, description, life cycle, and medical importance. It details the moth’s larvae, cocoons, pupae, and adult forms, highlighting their unique characteristics and behaviors. The article also discusses the moth’s natural enemies, including predators, pathogens, and parasitoids, and offers control measures for managing infestations. Additionally, it addresses the medical significance of the moth’s urticating hairs, which can cause dermatitis in humans. The document is intended for both laypersons and academic audiences interested in entomology.